The Diurnal Profile of Human Basal Pain Sensitivity and Skin Sympathetic Nerve Activity: A Healthy Volunteer Study - Zhu, Ying; Yan, Ai; Shu, Bin; Chen, Xuehan; Chen, Yupei; Duan, Guangyou; Huang, He (Frontiers in Neuroscience, 2022)
Objective: The diurnal rhythm profile of human basal pain sensitivity and its association with sympathetic nerve activity are not fully understood. This study aimed to include healthy volunteers to examine rhythmic changes in experimental pain sensitivity and skin sympathetic nerve activity. Methods: Thirty healthy volunteers were included in the study. Experimental pain sensitivity, including pressure pain threshold and tolerance, cold pain threshold and tolerance, skin sympathetic nerve activity, and cardiovascular parameters (including heart rate, cardiac output, and peripheral vascular resistance) at six time points throughout the day (08:00, 12:00, 16:00, 20:00, 00:00, and 04:00) were sequentially measured. Circadian rhythm analysis was performed on the mean values of the different measurements and individual subjects. Results: Significant differences were found in experimental pain sensitivity, skin sympathetic nerve activity, and noninvasive cardiovascular parameters at different time points (P<0.05). The minimum measured values of all four types of experimental pain sensitivity were consistently observed at 04:00. Rhythmical analysis showed that the mean values of pressure pain threshold (meta2d P=0.016) and skin sympathetic nerve activity (meta2d P=0.039) were significant. Significant diurnal rhythms in pain sensitivity and skin sympathetic nerve activity existed in some individuals, but not in others. No significant correlation between experimental pain sensitivity and skin sympathetic nerve activity was found at any time point (P>0.05). Conclusion: Significantly diurnal fluctuations were observed in different pain sensitivities and skin sympathetic nerve activity. No significant correlation between experimental pain sensitivity and sympathetic excitability at different times was found, and the reasons for these phenomena remain to be further studied.